Negotiating violence : Papal pardons and everyday life in East Central Europe (1450-1550) - Erdélyi, Gabriella (Brill, 2018)
This book examines the ways in which ordinary people used a transnational papal court of law for disputing their private local hostilities and for negotiating their social status and identities. Following the career and routine crossovers of runaway friars, the book offers vivid insights into the late medieval culture of violence, honour, emotions, learning and lay-clerical interactions. The story plays itself out in the large composite state of the Kingdom of Hungary and Croatia, which collapses under the Ottomans' sword in front of the readers' eyes. The bottom-up approach of the Christian-Muslim military conflict renders visible the rationalities of those commoners who voluntarily crossed the religious boundary, while the multi-tiered story convincingly drives home the argument that the motor of social and religious change was lay society rather than the clergy in this turbulent age.